Penerapan Pendekatan Kontekstual pada Pembelajaran PAI dalam Membentuk Moral Remaja di MTs Ainul Yaqin - Andika, M.; Ulin Nuha, Nazaha (Jurnal Pendidikan Islam, 2024)
The focus of individual education in Indonesia is on the maximun development of students based on their potential and societal values. The government, through Law No. 20 of 2003, regulates th national education system, emphasizing faith, piety, and noble character as the main competencies of graduates. Character education involves habituating good behavior, while Islamic religious education in schools aims to protect students from negative environmental influences. However, the effectiveness of religious education in shaping student behavior is being questioned. This study evaluates the effectiveness of contextual-based Islamic Regilious Education (PAI) in shaping the morals and character of students Mts Ainul Yaqin. The study employs qualitative methods through interviews and observations. The consequences display that the contextual approach helps students relate PAI material to  real-world   situations,   increases   student   engagement,   and Encourages the practice of Islamic  values in everyday life. Teachers play a crucial role in implementing this learning, with strategies that activate students and connect learning with real-life experiences. The findings suggest collaboration between teachers, parents as well as the neighborhood to support the formation of student character. Islamic regilious education has proven to be important in shaping adolescent morality and addressing student misconduct in schools.